Protein phosphatase 2A regulation of GABAB receptors normalizes ischemia-induced aberrant receptor trafficking and provides neuroprotection - Hleihil, Mohammad; Balakrishnan, Karthik; Benke, Dietmar (Frontiers in Molecular Neuroscience, 2022)
One major factor regulating the strength of GABAB receptor signaling and thereby neuronal excitability is the dynamic control of their cell surface expression. GABAB receptors are constitutively internalized and recycled back to the plasma membrane to maintain a stable number of receptors at cell surface for appropriate signaling. Protein phosphatase 2A (PP2A) dependent dephosphorylation of serine 783 (S783) in the GABAB2 subunit is a key event for downregulating GABAB receptor cell surface expression particularly under conditions associated with excitotoxicity. Here, we investigated the role of PP2A in regulating GABAB receptor cell surface expression under physiological and excitotoxic conditions. For this purpose, we developed an interfering peptide (PP2A-Pep) that inhibits the interaction of GABAB receptors with PP2A. Using cultured cortical neurons, we found that PP2A downregulates GABAB receptor cell surface expression by inhibiting recycling of the receptors and thereby promoting degradation of the receptors. Inhibition of the GABAB receptor/PP2A interaction by PP2A-Pep in cultured cortical neurons restored GABAB receptor cell surface expression after excitotoxic stress and inhibited progressing neuronal death even when added 48 h after the insult. To explore the therapeutic potential of PP2A-Pep, we further analyzed effect of PP2A-Pep in the middle cerebral artery occlusion (MCAO) mouse model of cerebral ischemia. Incubation of brain slices prepared from MCAO-treated mice with PP2A-Pep restored normal GABAB receptor expression and GABAB receptor-mediated inhibition, reduced ischemic-induced overexcitability of neurons, and prevented neuronal death in the ischemic penumbra. This data illustrates the crucial role of regulating GABAB receptor phosphorylation by PP2A for controlling neuronal inhibition and excitability. The results further suggest that interfering with the GABAB receptor/PP2A interaction is a promising strategy for the development of specific therapeutic interventions to treat neurological diseases associated with a disturbed excitation/inhibition balance and downregulation of GABAB receptors.